Jurnal Lindayasos Volume 22 No. 1 Juni 2023: Pemanfaatan Modal Sosial Dalam Pemasaran Produk Usaha Mikro di Desa Banjaran Kabupaten Majalengka. - Ujang, Ujang Muhyidin (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
In general, micro businesses have weaknesses in marketing including; product, price, place and promotion, so that it is slow in developing its business. Micro enterprises have social capital, namely trust, norms and networks that can be utilized. The purpose of this study was to find out and describe the utilization of micro-enterprise social capital in product marketing in Banjaran Village, Majalengka Regency. The method used in this research is descriptive - qualitative. The data sources used are purposive primary and secondary data sources. Data collection techniques used were in-depth interviews, observation, and documentation studies. The research results show; First, micro business marketing is still simple; unbranded product, no label, very simple packaging. Prices do not take into account similar products from competitors. Location of direct sales at production sites, traditional markets, neighboring stalls/shops. Promotion is done by word of mouth. Second, the social capital that is owned, starting from family, relatives, neighbors and friends of fellow micro-entrepreneurs, grows together with the customs of the people of Banjaran Village. Social capital forms networks, trust, social norms, both among workers and micro-entrepreneurs. Third, the use of social capital in the marketing strategy of micro-enterprises is in the form of good cooperation between them in producing, agreeing on product selling prices, joint sales, providing information and good communication with fellow micro-businesses and consumers. In conclusion, the marketing of micro business products in Banjaran Village, Majalengka Regency is still simple, they have quite good social capital and have been put to good use, the drawback is that they have limited knowledge about marketing.Keywords: Social Capital, Network, Norm, Micro Business, Marketing.